The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1161/jaha.121.021760
|View full text |Cite
|
Sign up to set email alerts
|

Intima Media Thickness and Cognitive Function Among Adults: Meta‐Analysis of Observational and Longitudinal Studies

Abstract: Background Carotid structural changes measured by intima media thickness (IMT) have been related to cognitive complaints during aging. Therefore, the aims of this meta‐analysis were (1) to elucidate the relationship between vascular status, measured as IMT, and cognitive domains distinguishing between global cognition, executive functions, memory and attention; and (2) to explore whether demographic (ie, age and sex), clinical (ie, body mass index and IMT baseline values), and procedure characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(67 reference statements)
0
3
0
3
Order By: Relevance
“…Hal ini mengindikasikan bahwa fungsi kognitif berkurang pada orang dengan penebalan CIMT. [32] Penelitian yang dilakukan oleh Frazier, dkk menunjukkan peningkatan nilai CIMT, yang merupakan penanda keadaan aterosklerosis, mengakibatkan penurunan fungsi kognitif bukan memori pada kelompok lanjut usia. [33] Penelitian lain melaporkan bahwa penebalan CIMT dan Flow-Mediated Dilation (FMD) berkaitan dengan fungsi neurokognitif yang lebih buruk pada keadaan obesitas dengan tekanan darah tinggi.…”
Section: Kesimpulanunclassified
See 2 more Smart Citations
“…Hal ini mengindikasikan bahwa fungsi kognitif berkurang pada orang dengan penebalan CIMT. [32] Penelitian yang dilakukan oleh Frazier, dkk menunjukkan peningkatan nilai CIMT, yang merupakan penanda keadaan aterosklerosis, mengakibatkan penurunan fungsi kognitif bukan memori pada kelompok lanjut usia. [33] Penelitian lain melaporkan bahwa penebalan CIMT dan Flow-Mediated Dilation (FMD) berkaitan dengan fungsi neurokognitif yang lebih buruk pada keadaan obesitas dengan tekanan darah tinggi.…”
Section: Kesimpulanunclassified
“…[33] Penelitian lain melaporkan bahwa penebalan CIMT dan Flow-Mediated Dilation (FMD) berkaitan dengan fungsi neurokognitif yang lebih buruk pada keadaan obesitas dengan tekanan darah tinggi. [32] Didapatkan pula hubungan yang kuat antara peningkatan CIMT dengan fungsi kognitif yang buruk di dalam populasi peminum alkohol. [34] Pemeriksaan fungsi kognitif menggunakan Mini-Mental State Examination (MMSE) yang dihubungkan dengan CIMT pada penelitian menggunakan analisis regresi linier multivariat didapatkan hubungan yang kuat antara CIMT dan fungsi kognitif pada kelompok dewasa muda dan lanjut usia di Republik Rakyat Tingkok.…”
Section: Kesimpulanunclassified
See 1 more Smart Citation
“…While cardiovascular disease remains the leading cause of death worldwide, the global burden of brain disease is rapidly increasing and is often associated with the same risk factors, as highlighted by the latest statistical update from the American Heart Association 1 . Indeed, known cardiovascular risk factors such as hypertension [2][3][4] , arterial stiffness [5][6][7] and atherosclerosis [8][9][10] , have been consistently associated with the pathogenesis of cerebrovascular disease (e.g., stroke and white matter lesions) and cognitive decline in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…The thickening of the arterial wall can be observed before the narrowing of the lumen and symptoms of the disease ( 10 ). Studies have previously demonstrated that carotid IMT is significantly associated with carotid plaque development, cardiovascular risk, and cognitive function ( 11 13 ). Moreover, a previous study found that the incidence of intracranial aneurysms in patients with IS was 6.6%, and the risk factors included female sex and old age ( 14 ).…”
Section: Introductionmentioning
confidence: 99%